2021
DOI: 10.17759/exppsy.2021140403
|View full text |Cite
|
Sign up to set email alerts
|

Mental Skills of an Athlete as a Resource of Professional Longevity in Sport

Abstract: The aim of the study was to assess associations between dimensions of mental skills, psychological readiness and predictors of career longevity among current athletes. Mental skills dimensions were measured with the Ottawa Mental Skills Assessment Tool (OMSAT). The psychological predictors of athletic career longevity were measured with the Athletic Coping Skills Scale-28 (the ACSI-28) producing scores for seven coping skills and with the Competitive State Anxiety Inventory-2 (CSAI-2) which produced scores for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…have higher scores than those who do not receive any support. In a study conducted by Bochaver et al (2021), it is indicated that receiving support from a sports psychologist or psychological performance counsellor positively affects mental skills such as imaging, coping with stress and anxiety, focusing and refocusing. Just like physical skills, psychological skills need to be studied systematically (Weinberg & Gould, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…have higher scores than those who do not receive any support. In a study conducted by Bochaver et al (2021), it is indicated that receiving support from a sports psychologist or psychological performance counsellor positively affects mental skills such as imaging, coping with stress and anxiety, focusing and refocusing. Just like physical skills, psychological skills need to be studied systematically (Weinberg & Gould, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…
Athletes with good mental skills or psychological skills perform better in tournaments and completing specific tasks in individual and team sports [1]. These improved mental abilities allow them to perform at their peak capacity, particularly in terms of self-confidence when competing in tournaments [2]. In addition, as compared to other athletes, these athletes have superior positive thinking capability and decision-making [3].
…”
mentioning
confidence: 99%